16 Days Campaign, Montenegro
“ELMAG” Radio, Montenegro, Morning program “Jutarnji program (te. ukljucenje) (Call-in program), 24.11.2002. (08:00-9:00), Theme: “Medun. Kampanja za borbu protiv nasilja nad zenama, 25.11.-10.12.2001. (International campaign about Violence against Women). Guest: Sanja Cejovic. Interview.